2008
DOI: 10.1093/rpd/ncn148
|View full text |Cite
|
Sign up to set email alerts
|

Double-dosimetry algorithm for workers in interventional radiology

Abstract: Based on double-dosemeter readings, a conservative effective dose (E) estimation algorithm for lead apron workers in interventional radiology is proposed. Typical radiation conditions for various exposure geometries were simulated using the MCNPX 2.4.0 code. The simulation model consisted of an X-ray source and image intensifier, a patient phantom and a voxelised staff member phantom with lead apron. The effective staff dose and dosemeter readings for several positions of the worker were calculated. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 11 publications
1
49
0
3
Order By: Relevance
“…Coefficients a 1 and a 2 according ICRP 60 (Table 3) are well within the range of the reported values. With the exception of one MC based algorithm with a 1 ϭ 1.64 (Clerinx et al 2008), the coefficients are in the range 0.5 Յ a 1 Յ 1.0 and 0.025 Յ a 2 Յ 0.075 for all algorithms (with thyroid shield; ICRP 1991). A Swiss regulation concerning personal dosimetry requires the use of double dosimetry for special working conditions and introduces Table 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coefficients a 1 and a 2 according ICRP 60 (Table 3) are well within the range of the reported values. With the exception of one MC based algorithm with a 1 ϭ 1.64 (Clerinx et al 2008), the coefficients are in the range 0.5 Յ a 1 Յ 1.0 and 0.025 Յ a 2 Յ 0.075 for all algorithms (with thyroid shield; ICRP 1991). A Swiss regulation concerning personal dosimetry requires the use of double dosimetry for special working conditions and introduces Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Routine measurement with two dosimeters was only recommended in one country. At the moment, various double dosimetry algorithms are available based on the effective dose concepts of ICRP 60 (1991) (Clerinx et al 2008;Järvinen et al 2008a and b) and ICRP 103 (2007) (von Boetticher et al 2008). Switzerland was the first European country to include an "official" double dosimetry algorithm for personal monitoring in its national radiation protection regulation (Swiss Ordinance 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] revealed that the doses to medical staff in interventional radiology and cardiology may be of concern from a radiation hygiene point of view. Partial-body doses reported ranged from a few microsieverts up to a few millisieverts per procedure, with higher values occurring mainly for the hands.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, other techniques to determine the real effective dose for medical staff have been recommended, e.g. measurement with two dosimeters [15,17] or calculation on the basis of the dose-area product (DAP) [3,5,6,11].…”
Section: Introductionmentioning
confidence: 99%